The voice of the past : oral history - Thompson, Paul, 1935-; Bornat, Joanna (Oxford oral history series., 2017)
Oral history and life stories, through recording the experiences of people of all kinds, invigorate both past and present, broadening life's base with unique testimony from hidden spheres of experience such as family relationships, the informal culture of work or the lives of migrants. This fully revised fourth edition of Paul Thompson's classic The Voice of the Past offers an invaluable tool for anyone using this approach.